Design of Patient Visit Recording Application Using the SDLC Method at Delia Hospital Based on Website - Sembiring, Mutiara br; Muhammad Zen; Hafni (Bahasa Indonesia, 2026)
The advancement of information technology has driven digital transformation across various sectors, including healthcare services in hospitals. One of the common issues faced is the management of patient data and visit records, which are still handled manually, resulting in slow data retrieval, higher risk of errors, and inefficiency. This study aims to design and develop a web-based patient visit recording application to improve the effectiveness of data management at Delia General Hospital. The system development method used in this study is the Software Development Life Cycle (SDLC), which consists of analysis, design, implementation, and testing stages. The developed system includes key features such as management of patient data, doctors, medications, polyclinics, laboratories, medical procedures, visits, medical records, and user management. The application is built using web-based technology, allowing easy access through computer networks. The results of this study indicate that the developed system is capable of managing data in an integrated manner, accelerating information retrieval, and minimizing recording errors. In addition, the system provides convenience for administrators in managing data through available create, read, update, and delete (CRUD) features. Therefore, this application can support improved efficiency and quality of administrative services in hospitals.